Association of Toll-like Receptor 4 Gene polymorphisms with susceptibility to type 2 diabetes mellitus in the Chinese population Toll样受体4基因多态性与中国人群2型糖尿病易感性的关联研究 - Peng, Danfeng; Jiang, Feng; Zhang, Rong; Tang, Shanshan; Chen, Miao; Yan, Jing; Sun, Xue; Luo, Yi; Hu, Cheng; Jia, Weiping (Journal of diabetes, 2015)
Background Toll‐like receptor 4 (TLR4) plays an important role in innate immunity. Activation of innate immune response and subsequent chronic low‐grade inflammation are thought to be involved in the pathogenesis of type 2 diabetes. In this study, we aimed to investigate the association of TLR4 variants with type 2 diabetes in the Chinese population. Methods Seven tag single nucleotide polymorphisms (SNPs) of TLR4 based on HapMap Chinese data were genotyped in the Shanghai Chinese, including 3404 type 2 diabetes patients and 3401 controls. The controls were extensively phenotyped for the traits related to glucose metabolism and insulin secretion. Results In total participants, we identified that rs10759932 and rs1927911 were associated with type 2 diabetes (odds ratio 1.106, P = 0.009 for rs10759532, odds ratio 1.092, P = 0.013 for rs1927911). rs11536889 showed a trend association with type 2 diabetes (odds ratio 0.957, P = 0.057). This SNP was also associated with 2‐h plasma glucose (P = 0.033) and high‐density lipoprotein‐cholesterol (P = 0.031). In female participants, rs10759932, rs1927911 and rs11536889 were associated with type 2 diabetes (odds ratio 1.176, P = 0.002 for rs10759932, odds ratio 1.136, P = 0.009 for rs1927911, odds ratio 0.882, P = 0.024 for rs11536889). Besides, rs11536889 was significantly associated with 2‐h plasma glucose (P = 0.050) and HOMA‐B (P = 0.046) with adjusting for age and body mass index in female normal subjects. Conclusions We conclude that genetic variants of TLR4 are associated with type 2 diabetes in the Chinese population, especially in female subjects. 摘要 背景： Toll样受体4（toll‐like receptor 4）在固有免疫中发挥重要作用。固有免疫的激活及其后续的慢性低度炎症可能也参与了2型糖尿病的发生。本研究旨在探讨中国人群中TLR4基因多态性与2型糖尿病的相关性。 方法： 研究对象来自中国上海，包括3404例2型糖尿病患者及3401例正常对照者。根据HapMap中国人数据库选取了7个TLR4的标签单核苷酸多态性（single nucleotide polymorphism，SNP），并对其在所有研究对象中进行基因分型。收集对照人群的葡萄糖代谢及胰岛素分泌相关的详细表型用于数量性状分析。 结果： 在总人群中，发现rs10759932和rs1927911均与2型糖尿病显著相关（rs10759932：OR，1.106，P = 0.009；rs1927911：OR，1.092，P = 0.013）。rs11536889与2型糖尿病有相关趋势（OR，0.957，P = 0.057），此位点与2小时血糖（P = 0.033）及高密度脂蛋白（P = 0.031）亦相关。在女性人群中，rs10759932、rs1927911及rs11536889均与2型糖尿病显著相关（rs10759932：OR，1.176，P = 0.002；rs1927911：OR，1.136，P = 0.009；rs11536889：OR，0.882，P = 0.024）。此外，在女性对照人群中，校正年龄及BMI后，rs11536889与2小时血糖（P = 0.050）及HOMA‐B（P = 0.046）显著相关。 结论： 在中国人群，尤其是女性人群中，TLR4基因变异与2型糖尿病发生风险相关。